Evaluation of a Digital Mammography System with the MAM-162 phantom - A. Castillo; N. A. Roas Zúniga (Brazilian Journal of Radiation Sciences)
Quality controls are performed to verify the performance status of X-ray equipment in relation to image quality and patient dose. Originally, the Laboratory of Radiation Physics and Metrology (LAF-RAM) in Nicaragua had only one phantom to evaluate mammography image quality subjectively; however, under a cooperation project with the International Atomic Energy Agency (IAEA), the MAM-162 phantom was acquired for the evaluation of physical image quality. In this work a CR type digital mammography system was evaluated using the MAM-162 phantom with adaptation to a single quality control protocol based on international standards such as the German Institute for Standardization (DIN) DIN 6868-162:2013-06, the IAEA technical document TECDOC protocol No. 1958 and the European Federation of Organizations for Medical Physics (EFOMP) mammo protocol. Among the main tests performed are the evaluation of the lateral image limit of the chest wall with satisfactory results, the automatic exposure control, the Signal-to-Noise difference ratio that complies with the tolerances, in the case Ghosting and dynamic range the results of both are satisfactory, the presence of artifacts was observed when applying variance mapping, a base value of the dynamic range was also obtained. For the dosimetry, the half value layer and the determination of the Mean Glandular Dose were evaluated, which does not comply with the tolerances. The final protocol document could be validated and implemented as part of the management and service documents of the Quality Control and Monitoring Laboratory (LCM) of LAF-RAM.